Consideration in Translating English/Chinese Contracts - Cao, Deborah (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1997)
AbstractThis paper addresses some of issues that have arisen in the English I Chinese translation of contracts. As Chinese and English are distinct in their linguistic, cultural and legal traditions, the problems confronting the legal translators are diverse and complex and they sometimes go beyond linguistic or translation boundaries. The paper discusses the areas of translation of legal concepts, legal language and cultural barriers with examples taken from actual practice. It argues that a sophisticated level of linguistic, cultural and legal knowledge is a prerequisite for an English / Chinese contract translator.